Drug repurposing of clinically approved drugs to target epithelial-mesenchymal transition using molecular docking approach - Chun Hao, Ong; Chau Ling, Tham; Harith, Hanis Hazeera; Firdaus, Nazmi; Ahmad Israf, Daud (Universiti Putra Malaysia Press, 2023)
Introduction: Epithelial-mesenchymal transition (EMT) is a process of epithelial transformation into mesenchymal cells. It is also a process that contributes to the progression of fibrosis and cancer metastasis. Transforming growth factor-beta (TGF-²), as a potent inducer of EMT, has therefore became a potential therapeutic target. However, clinical developments of TGF-² inhibitors have been un-successful due to safety risks. Hence, drug repurposing of existing safe-to-use drugs could over-come this issue. Methods: In this study, the TGF-² receptor type 1 (ALK5) was selected as the target protein. Molecular docking was performed using known ALK5 inhibitors as positive con- trols. Clinical drugs with similar binding affinity and amino acid interaction were selected for in vitro experimental validation. Results: ALK5 inhibitor demonstrated binding affinities ranging from -11.2 to -9.5 kcal/mol. Analysis of amino acid interaction revealed that Val219, Ala230, Lys232, and Leu340 amino acid residues are crucial for bind- ing. Subsequent screening of clinically approved drugs against ALK5 showed top five potential drugs (ergotamine, telmisartan, saquinavir, indinavir, and nelfinavir). The selected drugs were tested in TGF-²1-induced normal human bronchial epithelial cell line, BEAS-2B. Western blot analysis showed that the drugs did not exhibit inhibitory effects on the downregulation of epithelial proteins (E-cadherin) and upregulation of mesenchymal proteins (vimentin and ±-smooth muscle actin). Conclusion: Based on these experimental outcome, it is postulated that the results from mo- lecular docking were false positives. The tested drugs in this study could serve as negative controls in future screening against ALK5 protein.